Determining distinct roles of IL-1α through generation of an IL-1α knockout mouse with no defect in IL-1β expression - Malireddi, R.K. Subbarao; Bynigeri, Ratnakar R.; Kancharana, Balabhaskararao; Sharma, Bhesh Raj; Burton, Amanda R.; Pelletier, Stephane; Kanneganti, Thirumala-Devi (Frontiers in Immunology, 2022)
Interleukin 1α (IL-1α) and IL-1β are the founding members of the IL-1 cytokine family, and these innate immune inflammatory mediators are critically important in health and disease. Early studies on these molecules suggested that their expression was interdependent, with an initial genetic model of IL-1α depletion, the IL-1α KO mouse (Il1a-KOline1), showing reduced IL-1β expression. However, studies using this line in models of infection and inflammation resulted in contrasting observations. To overcome the limitations of this genetic model, we have generated and characterized a new line of IL-1α KO mice (Il1a-KOline2) using CRISPR-Cas9 technology. In contrast to cells from Il1a-KOline1, where IL-1β expression was drastically reduced, bone marrow-derived macrophages (BMDMs) from Il1a-KOline2 mice showed normal induction and activation of IL-1β. Additionally, Il1a-KOline2 BMDMs showed normal inflammasome activation and IL-1β expression in response to multiple innate immune triggers, including both pathogen-associated molecular patterns and pathogens. Moreover, using Il1a-KOline2 cells, we confirmed that IL-1α, independent of IL-1β, is critical for the expression of the neutrophil chemoattractant KC/CXCL1. Overall, we report the generation of a new line of IL-1α KO mice and confirm functions for IL-1α independent of IL-1β. Future studies on the unique functions of IL-1α and IL-1β using these mice will be critical to identify new roles for these molecules in health and disease and develop therapeutic strategies.